Second trimester extracellular microRNAs in maternal blood and fetal growth: An exploratory study - Rodosthenous, Rodosthenis S. (Epigenetics, 2017)
Healthy feto-maternal communication is critical during pregnancy and is orchestrated by the placenta. Dysfunction of the placenta leads to fetal growth complications; however, the underlying biological mechanisms have yet to be fully elucidated. Circulating extracellular microRNAs (exmiRNAs) in the blood have been implicated in cell-to-cell communication. Therefore, exmiRNAs may provide useful biological information about communication between the mother, the fetus, and the placenta during pregnancy. We used logistic regression to determine the association of exmiRNAs with abnormal fetal growth by comparing mothers of infants classified as small-for-gestational age (SGA) (n = 36) and large-for-gestational age (LGA) (n = 13) to appropriate-for-gestational age (AGA), matched by gestational age at delivery and infant sex. In addition, we used linear regression to determine associations between exmiRNAs and birth weight-for-gestational age (BWGA) z-score (n = 100), adjusting for maternal age, body mass index, and parity. We found that higher levels of miR-20b-5p, miR-942-5p, miR-324-3p, miR-223-5p, and miR-127-3p in maternal serum were associated with lower odds for having a SGA vs. AGA infant, and higher levels of miR-661, miR-212-3p, and miR-197-3p were associated with higher odds for having a LGA vs. AGA infant. We also found associations between miR-483-5p, miR-10a-5p, miR-204-5p, miR-202-3p, miR-345-5p, miR-885-5p, miR-127-3p, miR-148b-3p, miR-324-3p, miR-1290, miR-597-5p, miR-139-5p, miR-215-5p, and miR-99b-5p and BWGA z-score. We also found sex-specific associations with exmiRNAs and fetal growth. Our findings suggest that exmiRNAs circulating in maternal blood at second trimester are associated with fetal growth. Validation of our findings may lead to the development of minimally-invasive biomarkers of fetal growth during pregnancy.